2015
DOI: 10.1371/journal.pone.0133542
|View full text |Cite
|
Sign up to set email alerts
|

Stunting Is Associated with Food Diversity while Wasting with Food Insecurity among Underfive Children in East and West Gojjam Zones of Amhara Region, Ethiopia

Abstract: BackgroundFood insecurity has detrimental effects in protecting child undernutrition.This study sought to determine the level of child undernutrition and its association with food insecurity.MethodsA community based comparative cross-sectional study design involving multistage sampling technique was implemented from 24th of May to 20th of July 2013. Using two population proportion formula, a total of 4110 randomly selected households were included in the study. Availability of the productive safety net program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
120
4
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(173 citation statements)
references
References 24 publications
38
120
4
11
Order By: Relevance
“…The findings of this study were consistent with those of other local studies from East and West Gojjam, Ethiopia which reported a stunting prevalence of 37.5% and 38.3% among children from food secure and food insecure households (FSHHs and FIHHs), respectively and reported no significant variations among both groups [34]. This similarity may be due to contextual Hosmer-Lemeshow test p value=0.74 Time spent to water; the time it takes to reach to water source (for single trip) (1.00=Reference ***=p<0.001 ** =p<0.01 *= p<0.05) similarities in socio-demographic and economic characteristics, and feeding pattern of children of the study areas.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings of this study were consistent with those of other local studies from East and West Gojjam, Ethiopia which reported a stunting prevalence of 37.5% and 38.3% among children from food secure and food insecure households (FSHHs and FIHHs), respectively and reported no significant variations among both groups [34]. This similarity may be due to contextual Hosmer-Lemeshow test p value=0.74 Time spent to water; the time it takes to reach to water source (for single trip) (1.00=Reference ***=p<0.001 ** =p<0.01 *= p<0.05) similarities in socio-demographic and economic characteristics, and feeding pattern of children of the study areas.…”
Section: Discussionsupporting
confidence: 92%
“…According to this study finding, being a food secured household did not show any association with child stunting. This finding was in line with study reports from in Ethiopian and Brazil which showed the absence of association [34,51]. The absence of association might be because of other factors that directly or indirectly affect the nutritional status of children [52].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Low child DDS (≤4) in the current study was significantly associated with stunting status [AOR (95% CI) = 2.3 (1.2, 4.7)] suggesting that a diet habitually low in micronutrients may have contributed to stunting in the current study. DDS is a recommended qualitative indicator of micronutrient adequacy of a diet [27,45] and has been shown to predict growth of children in other studies [14,46,47]. On the other hand, DDS was not independently associated with wasting status; a similar finding to previous studies that reported DDS was associated with stunting, but not with wasting [14,46,47].…”
Section: Discussionsupporting
confidence: 76%